2016
DOI: 10.1038/eye.2015.274
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age, corneal astigmatism, and ocular dimensions with reference to astigmatism in eyes undergoing routine cataract surgery

Abstract: Purpose To assess the relationship between age, corneal astigmatism, and ocular dimensions with reference to astigmatism correction during cataract surgery. Methods In this cross-sectional study of right eyes of 2247 consecutive patients attending cataract surgery preassessment, data on patient demographics, axial length (AL), anterior chamber depth (ACD), and keratometric astigmatism were collected. Astigmatism was further analyzed as against-the-rule (ATR: steepest meridian 180 ± 30°), with-the-rule (WTR: 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 26 publications
5
30
1
Order By: Relevance
“…A shift from ATR to WTR with age was also detected (Supplementary Material Table 5), which is consistent with previous findings [15, 16].…”
Section: Resultssupporting
confidence: 92%
“…A shift from ATR to WTR with age was also detected (Supplementary Material Table 5), which is consistent with previous findings [15, 16].…”
Section: Resultssupporting
confidence: 92%
“…More and more studies have begun to pay attention to the relationship between age and corneal astigmatism. Similar findings showed that the magnitude of corneal astigmatism increased with increasing age [ 6 , 25 ]. In current study, interestingly, we found a stronger U-shaped association between corneal astigmatism and age ( Figure 3 ), which was not reported in most of the previous studies.…”
Section: Discussionsupporting
confidence: 75%
“…Although PL had the deepest ACD among our subgroups, it was still shallow when compared to the ACD in PL measured in prior studies (2.80–3.14 mm) [ 18 – 20 ]. This surprising finding may be explained firstly by the frequent mixed mechanisms that often underlie AAC.…”
Section: Discussioncontrasting
confidence: 69%